1989
DOI: 10.3109/02713688908997574
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Progesterone and Mifepristone on Intraocular Pressure in Rabbits

Abstract: The interaction between a topically administered progesterone, medrysone, and a steroid antagonist, mifepristone, on rabbit intraocular pressure (IOP) has been determined. Medrysone alone increased IOP significantly above parallel controls over the first three weeks; this increase was not sustained. When medrysone and mifepristone were given simultaneously the IOP increased initially, but then fell after two weeks to control levels. When mifepristone was added 14 days after medrysone, the IOP was again reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 7 publications
0
8
1
1
Order By: Relevance
“…= dexamethasone; RU486 = mifepristone. The more decisive results obtained with mifepristone [10] against progesterone stand in contradistinction to the present results. No obvious explanations exist for these dif ferences despite the use of drop application regimens, strain of rabbit and the use of a dexamethasone salt rather than an alcohol, that previously had resulted in an IOP in crease [14], The question of whether there is a potential role of mifepristone as a dexa methasone antagonist in the eye remains unanswered.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…= dexamethasone; RU486 = mifepristone. The more decisive results obtained with mifepristone [10] against progesterone stand in contradistinction to the present results. No obvious explanations exist for these dif ferences despite the use of drop application regimens, strain of rabbit and the use of a dexamethasone salt rather than an alcohol, that previously had resulted in an IOP in crease [14], The question of whether there is a potential role of mifepristone as a dexa methasone antagonist in the eye remains unanswered.…”
Section: Discussioncontrasting
confidence: 56%
“…Confirmation was made, by direct assay of radiolabeled material, of a pharmacologically active dose within the aqueous humor and ocular tissues [3], This compound has been shown to have excellent steroid antagonism in nonocular systems, es pecially against progesterone and dexameth asone [4][5][6][7][8][9]. In the eye, mifepristone antago nized the IOP elevation caused by progester one [10], although anomalous results were obtained when mifepristone was tested against dexamethasone in albino rabbits [11], In the latter study, a variable response was obtained to topical dexamethasone, making assessment of any antagonism by mifepristone difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Mifepristone (RU 486-6), a peripheral progesterone blocker with antiglucocorticoid properties, has been shown to reduce IOP in both normotensive 76 and corticosteroid-induced ocular hypertensive rabbits. 77 However, this mode of therapy has not yet been used in human subjects. Southren et al 78,79 have inhibited dexamethasoneinduced ocular hypertension in rabbits using tetrahydrocortisol.…”
Section: Future Therapiesmentioning
confidence: 99%
“…16 Similarly, topical administration of progesterone has been reported to increase IOP in rabbit eyes. 17 Ziai et al 10 reported that changes in IOP observed during pregnancy were associated with serum levels of progesterone. However, attempts to correlate endogenous levels of sex hormones (estrogen, progesterone, testosterone, FSH, and LH) during phases of the menstrual cycle and aqueous hemodynamics failed to demonstrate any significant associations.…”
mentioning
confidence: 98%